ANALYSIS OF SENTENCE CONNECTORS IN LYRIC SONGS OF BELIEVE ALBUM BY JUSTIN BIEBER - DARMAWATI .; FIMANDA ARLITA (JURNAL ILMIAH KOHESI, 2022)
This study deals with the use of sentence connectors in believe album by Justin Bieber. The purpose of this research was toinvestigate the types of sentence connectors, explain the types of sentence connectors, and explain why and how they arethe types of sentence connectors. The data in this study was taken from the lyrics song of Justin Bieber's "Believe" album.This study used a descriptive qualitative design. Therefore, when conducting this research, library research was applied toanalyze the data. I downloaded 13 lyric songs from Justin Bieber’s Believe album from the Internet. The data is divided intotwo types of sentence connectors, namely coordinate and subordinate. There were 63,49% for Coordinate type and 36,50%for Subordinate type. The dominant type is the coordinate type. The lyric song of Justin Bieber's "Believe Album" usedcoordinate and subordinate types to indicate that there are many references according to the meaning of the speaker, and itcan explain the words or sentences that the listener understands.